Integrated management of Phytophthora diseases in spices - Anandaraj, M; Bhai, R. Suseela (Indian Horticulture, 2019)
India is considered as the land of spices and the varying climates from tropical to subtropical to temperate favour the cultivation of one or the other spice crop. The most popular, export-oriented and most frequently used spices are black pepper, cardamom, chili, cinnamon, clove, nutmeg, mace, vanilla and seed spices such as coriander, cumin, fennel, and fenugreek besides herbal spices. The major production constraint in some of these spices is the diseases caused by Phytophthora. Spices are highly targeted by Phytopthora spp. causing serious havoc during monsoon season. Since they are export oriented and fetch a major portion of foreign exchange, the crop loss due to Phytopthora spp. leads to severe economic imbalance to the country.